Diffusion models under the solid phase control for adsorption and ion-exchange - Chourio, Edgar; Ferrer, Xiomara; Arrieta, Idelfonso; Fernández, Nola; Sarmiento, Cannen; García, Cézar (Rev. Téc. Fac. Ing. Univ. Zulia)
Diffusion Models under the Solid Phase Control for Adsorption and Ion-Exchange. In some adsorbents, the surface diffusion is the most important mechanism of intraparticle mass transfer. The correlation among particles of various shapes: spherical, cylindrical and planar, and the surface diffusion coefficient is well established. The optimum values of surface diffusion coefficient Dso are estimated by fitting the experimental adsorption kinetics reported in the literature with the present model developed, on basis to the combination between the exact solutions of the diffusion equations in solid and the optimization method of Davies. Swann Campey. The film resistence in not included. The validity of the diffusion model in transient regime is confirmed by comparison with the experimental data.